A novel aerodynamic drag-reduction mechanism using dolphin-inspired ultrasonic microvibrations - Dongyue Wang; Hao Liu (Scientific Reports)
Abstract Aerodynamic drag, particularly viscous drag, is a significant source of energy loss in aircraft, with its reduction being critical for improving overall aerodynamic performance. Here we introduce a novel strategy to reduce drag while enhancing lift-to-drag ratio by utilizing dolphin skin-inspired downstream-traveling longitudinal micro-ultrasonic waves (DTLMUWs). A turbulent drag reduction system was developed by applying DTLMUWs to the upper and lower surfaces of a NACA 0012 airfoil. Turbulent simulations at varying angles of attack (AoA) from 0° to 10° reveal that DTLMUWs excite a dynamic boundary layer that actively modulates turbulent velocity fluctuations within the viscous sublayer. This mechanism enables up to 90% reduction in total drag (friction and pressure drag), with minimal perturbation to the macro-flow around the airfoil. Consequently, a substantial increase in pressure-based lift is achieved, resulting in a more than tenfold improvement in lift-to-drag ratio at an AoA of 7.5°, and further enhancements at lower AoAs (2° to 5°) in level flight. These results present a transformative approach to drag reduction that could significantly advance aerodynamic design in aviation.